Higher incidence of acute kidney injury in patients treated with piperacillin/tazobactam than in patients treated with cefepime: a single-center retrospective cohort study - Shota Kadomura; Yoh Takekuma; Yuki Sato; Masato Sumi; Kotaro Kawamoto; Tatsuya Itoh; Mitsuru Sugawara (BMC, 2019)
Abstract Background Piperacillin/tazobactam (PIPC/TAZ) and cefepime (CFPM) are commonly used for the treatment of nosocomial and healthcare-associated infections. Recent reports have suggested that the incidence of acute kidney injury (AKI) in patients treated with a combination of vancomycin (VCM) and PIPC/TAZ is higher than that in patients treated with CFPM. However, there have been few reports on a comparison of the incidences of AKI in patients treated with PIPC/TAZ monotherapy and patients treated with CFPM. In this study, we investigated whether the incidence of AKI in patients treated with PIPC/TAZ is higher than that in patients treated with CFPM. Methods This study was a single-center retrospective observational study. Patients who died during the therapeutic period, patients younger than 18 years of age, and patients undergoing hemodialysis were excluded. Primary outcomes were the incidence of AKI and the AKIN stages defined by the Acute Kidney Injury Network. Secondary outcomes were discontinuation and/or change of antibiotics and initiation of dialysis due to AKI. We also investigated the time to onset and the risk factors of AKI in this population. Results There were 163 patients in the PIPC/TAZ group and 103 patients in the CFPM group. The incidence of AKI in patients treated with PIPC/TAZ (8.6%) was significantly higher than that in patients treated with CFPM (0.9%) (odds ratio (OR), 9.53; 95% confidence interval (CI), 1.41-408; p= 0.011). AKI severity was mostly stage 1 in both groups. There was no discontinuation and/or changes of antibiotics and there was no initiation of dialysis in either group. The onset of AKI in the PIPC/TAZ group (median period of 4 days) was earlier than that in the CFPM group. PIPC/TAZ was determined to be an independent risk factor of AKI in multivariate analysis (adjusted OR, 9.56; 95% CI, 1.21-75.3; p = 0.032). Conclusions This study showed that the incidence of AKI in patients who received PIPC/TAZ was higher than that in patients who received CFPM. Furthermore, the onset of AKI was earlier in patients who received PIPC/TAZ than in patients who received CFPM. PIPC/TAZ was an independent risk factor of AKI in this study population.